Numerical weather forecast model driven wheat blast disease early warning system for Bangladesh and Brazil - CGIAR Research Program on Wheat (2019)
This predictive model was developed based on analysis of historical epidemics and weather series data in the northern Paraná state in Brazil and then applied to Bangladesh. Expert national epidemiological knowledge of the meteorological conditions causing infections were also employed. This system is nationally endorsed for use in both countries.